The role of chemokines in leucocyte-stromal interactions in rheumatoid arthritis - Filer, Andrew (2008)
New dimensions in our understanding of immune cell trafficking in health and disease have been opened by the discovery of chemokines and their receptors. This family of chemo-attractant cytokines performs essential roles in the recruitment and subsequent positioning of leucocyte subsets within tissue microenvironments. Investigation of chemokine networks offers a novel approach to understand the mechanisms by which inflammatory cells persist in diseases such as rheumatoid arthritis (RA), where evidence is mounting that the inappropriate temporal and spatial expression of chemokines and/or their receptors may impair the resolution of leucocyte infiltrates. The recognition that stromal cells such as fibroblasts, as active components of tissue specific microenvironments, are able to determine the type and persistence of inflammatory infiltrates has opened new vistas in research. Stromal cells are active contributors to cytokine and inflammatory chemokine networks which result in immune cell recruitment and activation. However an intriguing role of stromal cells has been demonstrated in the inappropriate expression of constitutive, housekeeping chemokines, which contribute to the persistence of inflammation by actively blocking its resolution.